Egypt and the Hellenic economy: culture as a non-tariff trade barrier in the Atheno-Egyptian grain trade, 665-204BC - Cooper, CJ (2021)
Without sufficient food for her population, and in the absence of the empire which had sustained her before the Peloponnesian War, fourth-century BC Athens relied on regular supplies of foreign grain. While the trade in grain has been subjected to sustained scholarly interest, few academics have considered why Athens chose one grain source above another. Most agree that at least a third of Athens’ grain requirements were satisfied from the Euxine, which was vulnerable to infrequent crop failure and sits at the end of a precarious and navigationally challenging shipping route exposed to danger from the Spartans, Byzantians and pirates. Conversely, there is insufficient evidence that Egypt, a voluminous grain source closer (by ancient sailing practices) than the Black Sea, contributed much to Athens’ food supplies before the Battle of Chaironeia (338BC). This thesis contributes one solution to this conundrum: that cultural differences constituted such a significant transaction cost to Atheno-Egyptian trade that it outweighed the dangers of the Euxine route. Applying approaches derived from New Institutional Economics to the Atheno-Egyptian case-study, this thesis pre-empts the Finleyan shibboleth that ancient trade cannot be considered economically rational by demonstrating the real economic costs of linguistic, religious, ethnic, philosophical, governmental, diplomatic and legal differences. Through charting a gradual convergence in these areas between the seventh and third centuries BC, a new perspective is offered on Egypt’s transition into a Hellenic economy which undermines the long established ‘Classical’-‘Hellenistic’ and ‘Western’-‘Oriental’ dichotomies which still pervade literature on the ancient economy.